Analisis Manajemen Risiko Pembiayaan Cicil Emas di BSI KCP Waru Juanda - Danesh Ara Khayriya; Sri Wigati (Publikasi Inspirasi Indonesia, 2024)
Gold installment financing is a financing facility offered by sharia banking for gold ownership through installments using a murabahah contract and a rahn contract. The murabahah contract is used when the bank and the customer reach an agreement on the selling price of the gold itself. The bank will also obtain physical control rights from the customer, which will become a form of rahn contract in this financing. The aim of this research is to understand the risk management of gold installment financing at BSI KCP Waru Juanda. The subject of this research is Bank Syariah Indonesia KCP Waru Juanda. Meanwhile, in this research, the object studied is the risk management of one of the financing products at BSI KCP Waru Juanda, namely gold installment financing. This study used qualitative research methods. Research data was collected from interviews, observations and documentation. Apart from that, the researcher also used several literature studies related to this research as reference material.